PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR KOMISI PEMILIHAN UMUM (KPU) KABUPATEN KERINCI - ALSUNAH, M DHANY (journal of RESIDU, 2018)
The purpose of this research is for find information about The effect of discipline  work to the control work of worker  at all of Komisi Pemilihan Umum of Kerinci regency, for find the information how big The effect of discipline  work to the control work of worker  at all of Komisi Pemilihan Umum of Kerinci regency. The kind of this research is quantitative research where speak by using numbers and also see the Influence between free variable (Independent) with connection variable (dependent) at this research the researcher want to know to see t The effect of discipline  work to the control work of worker  at all of Komisi Pemilihan Umum of Kerinci regency. The result of this research is there is The effect of discipline  work to the control work of worker  at all of Komisi Pemilihan Umum of Kerinci regency that count with correlation of the mistakes level 0,541, constant there is 3,682 The effect of discipline  work to the control work of worker  at all of Komisi Pemilihan Umum of Kerinci regency is significant 0,05/ 5%. The big of The effect of discipline  work to the control work of worker  at all of Komisi Pemilihan Umum of Kerinci regency is 70,3 % and the residue is 20,8 % have Influenced by other variable that not researched.   Keyword : control work and discipline work.